Industrial guideline for injection moulding: case of jaundice meter - Naqibah, Azman; Nik Hisyamudin, Muhd Nor; Mohd Fahrul, Hassan; Mohd Hafiz, Burhan; Siti Zarina, Mohd Muji; Fariza, Mohamad; Faiz, Mohd Turan; Abdul Rahman, Bahasa; Seiji, Yokoyama (The World Academy of Research in Science and Engineering, 2020)
In designing industries, a lot of measures need to be taken before coming to the final design phase. During the initial stage of designing a product, designers usually will design according to their sketching without considering guidelines for mass production manufacturing. This will consume soo much time on re-designing for to suit manufacturing requirement. There-fore this paper purpose to consider industrial guideline specifically on designing product directly for injection moulding. The most basic requirement on design for direct manufacturing that designers need to consider while designing are wall thick-ness, rib, boss and cored holes, suggested design for corners and materials selection. The guideline was applied to a jaun-dice meter prototype design as a case study.